(untitled) (Conferencea, 2023)
Female freestyle wrestling demands peak physical performance and stamina. Sustained energy levels are vital for athletes to excel in both training and competition. This article delves into the development of nutritional guidelines and dietary plans specifically tailored to the unique needs of female freestyle wrestlers. It explores the role of macronutrients, micronutrients, hydration, and meal timing in optimizing energy levels and supporting overall health. By drawing from the expertise of sports nutritionists, experienced wrestlers, and coaches, this article provides a comprehensive overview of evidence-based nutritional strategies designed to enhance endurance and performance in the world of female freestyle wrestling.